Energy–environmental nexus in green hydrogen-assisted conversion of second-crop canola to sustainable aviation fuel: Toward low-carbon bioenergy systems - Giulia Cruz Lamas; Alexandre Nunes Cardoso; Priscila Seixas Sabaini; Sandra M. Luz; Maria dos Reis Santos Borges; Tainara da S. Costa; Thiago da Silva Gonzales; Marilia Ieda da Silveira Folegatti Matsuura; Bruno Galveas Laviola; Thiago O. Rodrigues; Patrick Rousset; Edgar A. Silveira (Biomass and Bioenergy, 2026)

Effect of torrefaction severity on the energy recovery from amazonian wood residues for decentralized energy conversion systems - Edgar A. Silveira; Giulia Cruz Lamas; Pedro Paulo de O. Rodrigues; Normando P.B. Souto; Bruno Sant’Anna Chaves; Luiz Gustavo Oliveira Galvão; Lucélia A. Macedo; Juliana Sabino Rodrigues; Sandra M. Luz; Patrick Rousset; Thiago de Paula Protásio (Biomass and Bioenergy, 2025)

Highly efficient and sensitive membrane-based concentration process allows quantification, surveillance, and sequencing of viruses in large volumes of wastewater - G El soufi; L Di Jorio; Z Gerber; N Cluzel; J Van Assche; D Delafoy; R Olaso; C Daviaud; T Loustau; C Schwartz; D Trebouet; O Hernalsteens; et al. (Water Research, 2024)

Optimization of multi-environment trials for genomic selection based on crop models - R. Rincent; E. Kuhn; H. Monod; F.-X. Oury; M. Rousset; V. Allard; J. Le Gouis (Theoretical and Applied Genetics, 2017)

Bread wheat milling behavior: effects of genetic and environmental factors, and modeling using grain mechanical resistance traits - François-Xavier Oury; P. Lasme; C. Michelet; A. Dubat; O. Gardet; E. Heumez; B. Rolland; M. Rousset; J. Abecassis; C. Bar L’Helgouac’h; V. Lullien-Pellerin (Theoretical and Applied Genetics, 2017)

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

Relationships between wheat grain physical characteristics studied through near-isogenic lines with distinct puroindoline-b allele - François-Xavier Oury; P. Lasme; C. Michelet; M. Rousset; J. Abecassis; V. Lullien-Pellerin (Theoretical and Applied Genetics, 2015)

Stable coexistence of incompatible Wolbachia along a narrow contact zone in mosquito field populations - Célestine M. Atyame; Pierrick Labbé; François Rousset; Marwa Beji; Patrick Makoundou; Olivier Duron; Emilie Dumas; Nicole Pasteur; Ali Bouattour; Philippe Fort; Mylène Weill (Molecular Ecology, 2015)
In arthropods, the intracellular bacteria W olbachia often induce cytoplasmic incompatibility ( CI ) between sperm and egg, which causes conditional embryonic death and promotes the spatial spread of W olbachia infections into host populations. The ability of W olbachia to spread in natural populations through CI has attracted attention for using these bacteria in vector‐borne disease control. The dynamics of incompatible W olbachia infections have been deeply investigated theoretically, whereas in natural populations, there are only few examples described, especially among incompatible infected hosts. Here, we have surveyed the distribution of two molecular W olbachia strains ( w P ip11 and w P ip31) infecting the mosquito C ulex pipiens in T unisia. We delineated a clear spatial structure of both infections, with a sharp contact zone separating their distribution areas. Crossing experiments with isofemale lines from different localities showed three crossing types: w P ip11‐infected males always sterilize w P ip31‐infected females; however, while most w P ip31‐infected males were compatible with w P ip11‐infected females, a few completely sterilize them. The w P ip11 strain was thus expected to spread, but temporal dynamics over 7 years of monitoring shows the stability of the contact zone. We examined which factors may contribute to the observed stability, both theoretically and empirically. Population cage experiments, field samples and modelling did not support significant impacts of local adaptation or assortative mating on the stability of w P ip infection structure. By contrast, low dispersal probability and metapopulation dynamics in the host C x. pipiens probably play major roles. This study highlights the need of understanding CI dynamics in natural populations to design effective and sustainable W olbachia ‐based control strategies.

Genome-wide association analysis to identify chromosomal regions determining components of earliness in wheat - J. Le Gouis; J. Bordes; C. Ravel; E. Heumez; S. Faure; S. Praud; N. Galic; C. Remoué; F. Balfourier; V. Allard; M. Rousset (Theoretical and Applied Genetics, 2012)

Grain characterization and milling behaviour of near-isogenic lines differing by hardness - V. Greffeuille; J. Abecassis; M. Rousset; F.-X. Oury; A. Faye; C. Bar L’Helgouac’h; V. Lullien-Pellerin (Theoretical and Applied Genetics, 2006)

Detection and mapping of QTL for earliness components in a bread wheat recombinant inbred lines population - E. Hanocq; M. Niarquin; E. Heumez; M. Rousset; J. Le Gouis (Theoretical and Applied Genetics, 2004)

FTIR spectroelectrochemical study of the activation and inactivation processes of [NiFe] hydrogenases: effects of solvent isotope replacement and site-directed mutagenesis - Antonio L. De Lacey; Alejandro Pardo; Víctor M. Fernández; Sebastian Dementin; Geraldine Adryanczyk-Perrier; E. Claude Hatchikian; Marc Rousset (JBIC Journal of Biological Inorganic Chemistry, 2004)

Spectroscopic and kinetic characterization of active site mutants of Desulfovibrio fructosovorans Ni-Fe hydrogenase - Antonio L. De Lacey; Victor M. Fernandez; Marc Rousset; Christine Cavazza; Claude E. Hatchikian (JBIC Journal of Biological Inorganic Chemistry, 2003)

Use of recombinant substitution lines for gene mapping and QTL analysis of bread making quality in wheat - M. Rousset; P. Brabant; R.S. Kota; J. Dubcovsky; J. Dvorak (Euphytica, 2001)

Comparisons of recombination frequencies in hybrids involving telocentric and bibrachial wheat chromosomes - J. Dubcovsky; G. Tranquilli; I. A. Khan; L. A. Pflüger; E. Suárez; M. Rousset; J. Dvorak (Theoretical and Applied Genetics, 2000)

Comparative analysis of microsatellite and allozyme markers: a case study investigating microgeographic differentiation in brown trout ( Salmo trutta ) - A. ESTOUP; F. ROUSSET; Y. MICHALAKIS; J.‐M. CORNUET; M. ADRIAMANGA; R. GUYOMARD (Molecular Ecology, 1998)

Migration/selection balance and ecotypic differentiation in the mosquito Culex pipiens - C. CHEVILLON; Y. RIVET; M. RAYMOND; F. ROUSSET; P. E. SMOUSE; N. PASTEUR (Molecular Ecology, 1998)
Ecotypic differentiation is well described in the mosquito Culex pipiens , separating populations breeding in subterranean and human‐made sites (hypogeous habitat) from those in open‐air sites (epigeous habitat). The pattern of population differentiation observed at the Aat‐1 locus has been suspected to be associated with such ecotypic differentiation via habitat‐dependent selection, but this supposition is still the subject of debate in the literature. We analysed differentiation patterns for Aat‐1 and another four loci among populations from both habitat types in the French Alps. We showed that the Aat‐1 A allele is favoured within hypogeous habitats but selected against within epigeous habitats. Comparisons of our results with other data reported in the literature indicate that the Aat‐1 A allele is generally evolving under habitat‐differential selection, but that the precise balance of migration and selection that determines equilibrium allele frequencies varies greatly across Europe. The nature of this habitat‐dependent selection, and its resulting (geographically varying) equilibrium point, are discussed in relation to the biology of this mosquito species.

Seed-storage-protein loci in RFLP maps of diploid, tetraploid, and hexaploid wheat - J. Dubcovsky; M. Echaide; S. Giancola; M. Rousset; M. C. Luo; L. R. Joppa; J. Dvorak (Theoretical and Applied Genetics, 1997)

Physiological characteristics and growth behavior of single and double hydrogenase mutants of Desulfovibrio fructosovorans - Souria Malki; Gilles De Luca; Marie Laure Fardeau; M. Rousset; Jean Pierre Belaich; Z. Dermoun (Archives of Microbiology, 1997)